2011
DOI: 10.3390/cancers3010510
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor in Cancer Cell Death and Survival

Abstract: One of the major challenges for cancer therapeutics is the resistance of many tumor cells to induction of cell death due to pro-survival signaling in the cancer cells. Here we review the growing literature which shows that neurotrophins contribute to pro-survival signaling in many different types of cancer. In particular, nerve growth factor, the archetypal neurotrophin, has been shown to play a role in tumorigenesis over the past decade. Nerve growth factor mediates its effects through its two cognate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 118 publications
8
104
1
1
Order By: Relevance
“…Specifically, nerve cells secret a number of cytokines that promote the growth and invasion of tumor cells (19,20). Moreover, tumor cells improve the growth of nerve cells by secreting a number of cytokines, such as neurotrophic factors, chemokines, and nerve adhesion factors (1,17,21,22). It has been reported previously that some tumor-derived cytokines are involved in the development and invasion of pancreatic and head and neck cancers (4,5,23,24), however, the role of tumor-derived cytokines in the invasion of cervical cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, nerve cells secret a number of cytokines that promote the growth and invasion of tumor cells (19,20). Moreover, tumor cells improve the growth of nerve cells by secreting a number of cytokines, such as neurotrophic factors, chemokines, and nerve adhesion factors (1,17,21,22). It has been reported previously that some tumor-derived cytokines are involved in the development and invasion of pancreatic and head and neck cancers (4,5,23,24), however, the role of tumor-derived cytokines in the invasion of cervical cancer is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing literature to suggest that neurotrophins are involved in pro-survival signalling in many different forms of cancer. (55) (56,57) NGF was seen to be prevalent in both normal and tumorigenic prostate tissue in a study by Geldof et al (1998). (56) One study demonstrated higher intensity staining for NGF/TrkA in oral tongue SCC with PNI (n=21) compared to those without PNI (n=21).…”
Section: Neurotrophins and The Trk Receptor Familymentioning
confidence: 99%
“…P75 interacts with caveolin following TNF-α and NFKβ activation 158 . NFG was discovered from sarcoma while human colon cancer biopsy revealed TrkA and P75 was isolated from human melanoma cell lines 159 . In breast cancer there is increase in NGF expression leading to phosphorylation mitogenesis, invasion, metastasis and angiogenesis via activation of all the three pathways i.e MAPK, PI3K/AKT and PLCγ 160 .…”
Section: Neurotrophin Familymentioning
confidence: 99%